Comprehensive Transcriptome-Wide Profiling of 5-Methylcytosine Modifications in Long Non-Coding RNAs in a Rat Model of Traumatic Brain Injury - Zhijun Xiang; Yixing Luo; Jiangtao Yu; Haoli Ma; Yan Zhao (Current Issues in Molecular Biology)
Traumatic brain injury (TBI) poses a major global health challenge, leading to serious repercussions for those affected and imposing considerable financial strains on families and healthcare systems. RNA methylation, especially 5-methylcytosine (m5C), plays a crucial role as an epigenetic modification in regulating RNA at the level of post-transcriptional regulation. However, the impact of TBI on the m5C methylation profile of long non-coding RNAs (lncRNAs) remains unexplored. In the present study, we conducted a thorough transcriptome-wide examination of m5C methylation in lncRNAs in a rat TBI model utilizing MeRIP-Seq. Our results revealed significant differences in the amount and distribution of m5C methylation in lncRNAs between TBI and control groups, indicating profound changes in m5C methylation following TBI. Bioinformatic analyses linked these specifically methylated transcripts to pathways involved in immune response, neural repair, and lipid metabolism, providing insight into possible mechanisms underlying TBI pathology. These findings offer novel perspectives on the post-transcriptional modifications in lncRNA m5C methylation following TBI, which may contribute to understanding the disease mechanisms and developing targeted therapeutic strategies.